Exploring the Validity, Reliability and Normal Scores of Oral-Speech Motor Control Protocol in Farsi-Speaking Children in Isfahan - Yalda Kazemi; Fatemeh Derakhshandeh (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: Current study took place in order to deliver a comprehensive assessment of oral and speech motor abilities in verbal and non-verbal tasks in normally children based on oral/speech motor control protocol and determination of this protocol validity and reliability after translation. Materials & Methods: First stage of this research was a descriptive study and validity assessment and in second stage it was done cross - sectional and comparatively. After translating the protocol into Farsi, some items relating to speech coordinated movements were modified to conform in Farsi. Three hundred normally Farsi speaking children were selected by radom sampling from day care centers and preschool classes. The means and standard deviations of the main variables were computed and some comparisons were analyzed by using one-way ANOVA. Results: The scores of 5-6 years children usually was more than other groups and their difference was significant (P<0/001). Reliability coefficient of protocol in different age groups were 0/19-0/59 in TSS and 0/75-0/80 in TFS. Conclusion: The results imply a meaningful increase in TFS, and MPT scores by age groups and decrease in TSS and imply increase in speech functions. This protocol can be used in researches and clinical evaluations.